Growing Age and Education Gaps?: The Evolution of Partisan Vote Choice among Religious Voters in the U.S., 2008-2018 - Hansen, Eric R. (Journal of religion & society. Supplement, 2021)
Over the last three decades, two divergent trends help to explain voter support for the two political parties. Voter support for each party by religious affiliation has remained remarkably stable. In contrast, coalitions of party support seem to be shifting along the lines of age and educational attainment, with younger voters and college educated voters increasingly likely to support Democratic candidates. In this research we examine how age and education condition support for the political parties within religious traditions. We draw upon survey data from the 2008–2018 waves of the Cooperative Congressional Election Study (CCES). Our findings suggest that among faith traditions with generally higher levels of support for Democratic candidates, there are small differences between younger and older adherents. Similar small differences are observed between college educated and other voters. However, among faith traditions with higher levels of support for the Republican Party, we find growing rifts between young and old voters. We also find disparate trends in support between college educated and non-college educated voters. We identify the implications for these findings moving forward.